ANALISIS PENGARUH PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS (Studi Pada Bank Umum Syariah Yang Terdaftar Di Bursa Efek Indonesia) - siti mujtarifah; sri nuringwahyu; Ratna Nikin Hardati (JIAGABI (Jurnal Ilmu Administrasi Niaga/Bisnis), 2020)
This study aims to determine the effect of Mudharabah financing and musharaka financing on the profitability of Sharia Commercial Banks in the 2016-2018 period. This type of research is quantitative. The method used in data collection is the documentation method. The data used is the quarterly financial statements of Islamic Commercial Banks starting from 2016 to 2018. The number of samples is 102 and using the method of multiple linear regression analysis. Data processing using SPSS 16.0 for Windows. The results showed that in the t test partially Mudharabah financing variables had a significant positive effect on profitability. Musyarakah  financing variable has a significant negative effect on profitability. The F test simultaneously shows that the Mudharabah financing variable and the Musyarakah  financing variable have a significant positive effect on profitability. The dominant variable in the study is the Musyarakah  financing variable.